Pengaruh Polaritas Arus Dan Kecepatan Pengelasan Menggunakan Sistem Sliding Adaptive Vertical Pada Pengelasan Smaw Terhadap Hasil Pengelasan - Alfadeny Anjer Farino; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
SMAW (Shield Metal Arc Welding) is one of the commonly used welding technology because it has an excess of which easy to use at any thickness, easy to use with all the welding position and the flow can be varied. In this research,a welding machine of SMAW used Adaptive Vertical Sliding System, so that the welding speed can be arranged constant. This research used a variation of the DC flow (reverse polarity and straight polarity) and the speed of welding based on the welding results by conducting of visual testing, penetrant testing, tensile testing and metalografi testing. The welding speed was controlled using the arduino uno,which linked to motor stepper as the Activator. The Materials used was low carbon steel (mild steel), the groove was used a single v groove of 60 ° and an electrode of E6013. There were 18 specimens to be tested, which 9 of specimens using the straight polarity and 9 of specimens using the reverse polarity. The highest tensile strength of whole specimens occur on straight polarity specimens of 490.95 MPa and the lowest tensile strength specimens occur in the reverse polarity of 283.47 MPa. The micro structure was determined by many factors such as heat input, flow, the speed of the welding, and the rate of cooling. In this research HAZ areas has a larger grain structure than base metal and weld metal.Keywords: Welding, Tensile Testing, Penetrant Testing, Metalografi, HAZ